2D and 3D photonic crystal materials for photocatalysis and electrochemical energy storage and conversion. Issue 1 (1st December 2016) - Collins, Gillian; Armstrong, Eileen; McNulty, David; O'Hanlon, Sally; Geaney, Hugh; O'Dwyer, Colm
Abstract: This perspective reviews recent advances in inverse opal structures, how they have been developed, studied and applied as catalysts, catalyst support materials, as electrode materials for batteries, water splitting applications, solar-to-fuel conversion and electrochromics, and finally as photonic photocatalysts and photoelectrocatalysts. Throughout, we detail some of the salient optical characteristics that underpin recent results and form the basis for light-matter interactions that span electrochemical energy conversion systems as well as photocatalytic systems. Strategies for using 2D as well as 3D structures, ordered macroporous materials such as inverse opals are summarized and recent work on plasmonic–photonic coupling in metal nanoparticle-infiltrated wide band gap inverse opals for enhanced photoelectrochemistry are provided. Abstract :